1980
DOI: 10.1126/science.7434000
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Potentials Generated in the Human Hippocampal Formation and Amygdala by Infrequent Events

Abstract: Infrequent, attended, auditory and visual stimuli evoke large potentials in the human limbic system in tasks that usually evoke endogenous potentials at the scalp. The limbic potentials reverse polarity over small distances and correlate with unit discharges recorded by the same electrodes, indicating that they are locally generated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
291
5
8

Year Published

1988
1988
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 759 publications
(332 citation statements)
references
References 12 publications
28
291
5
8
Order By: Relevance
“…This finding may seem surprising in view of reports that electrical activity is generated within medial temporal lobe structures coincident with scalp-recorded P3 waves in humans (Halgren et al, 1980;Okada et al, 1983;Wood et al, 1984).…”
Section: An Animal Model Ofp3mentioning
confidence: 68%
“…This finding may seem surprising in view of reports that electrical activity is generated within medial temporal lobe structures coincident with scalp-recorded P3 waves in humans (Halgren et al, 1980;Okada et al, 1983;Wood et al, 1984).…”
Section: An Animal Model Ofp3mentioning
confidence: 68%
“…Visual inspection of the Tarkka & Stokic (1998) waveforms indicates that P2/N2 ERPs at lateral central sites appeared to be more positive in the single-tone than the two-tone task (Katayama & Polich, 1996). It is also noteworthy that P3 activity may be linked to medial temporal lobe generators (Halgren, 1980). Therefore, it is plausible that modulations in hemodynamic activity in the temporal lobe could be ascribed to any of the N1, P2, N2, and P3 ERPs.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, target stimuli produced activity in the ventral frontotemporal cortices, superior temporal sulcus, posterior parietal cortex, and the hippocampus, suggesting that these areas are neural generators associated with target-elicited P3 ERPs (Baudena et al, 1995;Halgren, 1980;Halgren et al, 1995a;Halgren et al, 1995b; Halgren et al, 1998). Halgren and colleagues concluded that widespread brain activation involves integration of stimulus processing and context, which is necessary for the online monitoring of performance.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, patients with focal hippocampal lesions evinced reduced P3a amplitude from novel distracters but normal P3b components from targets (Knight, 1996). Initial studies of the hippocampal formation using depth electrodes in humans suggested that at least some portion of the P300 (P3b) is generated in the medial temporal lobe (Halgren et al, 1980;McCarthy et al, 1989). However, subsequent reports of scalp recordings from individuals after temporal lobectomy (Johnson, 1988b;Smith and Halgren, 1989), experimental excisions in monkeys (Paller et al, 1988(Paller et al, , 1992, and patients with severe medial temporal lobe damage (Onofrj et al, 1992;Rugg et al, 1991) found that the hippocampal formation does not contribute directly to P300 generation (Molnar, 1994).…”
Section: Neural Origins Of P3a and P3bmentioning
confidence: 99%